Analysis of government development financing between Sukuk and Bonds. Issue 1 (March 2020) - Alimuddin; Putri, N A; Nurleni
Abstract: This study aims to examine the performance of government development financing sukuk/SBSN compared with bonds/SUN period 2014-2017. The method used is descriptive quantitative with secondary data. The data obtained were analyzed and concluded based on a predetermined framework. The results of the analysis based on the method of efficiency ratio, Data Envelopment Analysis (DEA) and Value at Risk (VaR) shown that SUN has high efficiency and high risk, while SBSN has low efficiency and low risk. Based on the analysis of the Efficient Portfolio Frontier shown that an efficient portfolio exists at risk level to 0.14% and profit rate up to 369.31% exist in the proportion of 60% SBSN financing and 40% SUN financing proportion, it means that the Sukuk financing portfolio was better rather than Bonds financing portfolio.